The Constitutional Implications of Constitutional Court Decision No. 90/PUU-XXI/2023 on National Democratic Stability - Jibril Makarim; Ahmad Ahmad; Muhammad Rizqi Ramadhan; Agis Syadina Putra; Endang Mulyadin (Universitas Muhammadiyah Tangerang, 2025)
The decision of the Constitutional Court No. 90/PUU-XXI/2023 on the age requirement for presidential and vice-presidential candidates has generated significant controversy in constitutional law, particularly regarding democratic stability. The ruling modified the statutory minimum age of 40 by allowing individuals who have held or currently hold elected public office to run, even if they are below that threshold. The judicial review was filed by Almas Tsaqibbirru Re A to support Gibran Rakabuming Raka in the 2024 election. This study adopts a normative juridical approach with a descriptive-qualitative method based on literature review. The findings reveal substantial weaknesses in the petitioner’s legal standing, as no direct constitutional harm was demonstrated. Nevertheless, the Court partially granted the petition and went beyond its original claims, effectively creating a new norm. In doing so, the Court shifted from its role as a negative legislator to a positive legislator, raising concerns over the separation of powers. The ruling carries broad constitutional and political implications, simultaneously enabling leadership regeneration while inviting suspicions of political interests. Internal divisions among the justices further reflect a lack of strong consensus. Criticism intensified after the Constitutional Court Honorary Council confirmed ethical violations in the decision-making process.